Psychological Concerns of Children Undergoing Kidney Transplantation During the Pandemic: Single-centre Experience - Stephen Marks; Nicos Kessaris; Jelena Stojanovic; Alicia Paessler; Sheila Boyle (BMJ Publishing Group, 2021)
Many paediatric kidney transplant programmes were closed during the COVID-19 pandemic, and due to the vulnerable nature of patients with end-stage kidney disease (ESKD), there were new concerns once these programmes reopened. We surveyed children and families who received a kidney transplant during the pandemic. We found that half of the participants felt scared and/or anxious about receiving a kidney transplant during the pandemic, and 2/8 participants were worried about catching COVID-19 during their recovery. While detailed counselling and additional safety precautions contributed to a good experience, patients and parents still demonstrated fear towards transplantation.